Müstakimzâde’ye Göre Nakşbendiyye’nin Bilinmeyen On İkinci Esası/ The Unknown Twelfth Principle of Naqshibandiyya According to Mustaqeemzadah - incebilir, uğur (Journal of History Culture and Art Research, 2015)
The Unknown Twelfth Principle of Naqshibandiyya According to Mustaqeemzadah Abstract There are eleven principles in Hacegan-Naqshibandiyya tariq that are known as “kalimat el-qudsiyya” (the divine words). However Mustaqeemzade Suleiman Sadeddin Effendi, one of the shaykhs of Hacegan-Naqshibandiyya-Mujaddidiyya tariq, mentions another principle which differs from the eleven principles of the above-cited tariq. This is the first time for us to come accross such a principle mentioned, maybe not as a technical term but as an independent principle. As a matter of fact he indicates that this is not a well-known principle by noting down in one of his work saying that “it seems exclusive for this work”. In this article, “kalimat al-qudsiyya” (the divine words) based on the work of Mustaqeemzade will be described and additionally his statements and views regarding the previously mentioned twelfth principle will be introduced. Besides, different sources were used to make the topic better understood. Müstakimzâde’ye Göre Nakşbendiyye’nin Bilinmeyen On İkinci Esası Öz Hâcegân-Nakşbendiyye tarîkinde kelimât-ı kudsiyye ismiyle bilinen on bir esas vardır. Ancak 18. asırda yaşamış olan Hâcegân-Nakşbendiyye-Müceddidiyye meşâyıhından Müstakimzâde Süleyman Sa’deddîn Efendi (1131-1202/1719-1788), mezkûr tarikatteki on bir esasa ilaveten bir esasın daha olduğundan bahseder ki ıstılah olarak olmasa da müstakil bir esas olarak kullanımına ilk kez Müstakimzâde’de tesadüf etmekteyiz. Kendisi de zaten bu esasın pek bilinmediğini belirtmekte, bir eserinde derkenar olarak düştüğü notta “bu cerideye münhasır gibidir” ifadesiyle tasrih etmektedir. Bu makalemizde Müstakimzâde’nin eserlerinde geçtiği hâli merkez alınarak kelimât-ı kudsiye tarif edilip akabinde bahsi geçen on ikinci esas ile ilgili ona ait söz ve görüşler ortaya konmaya çalışılacaktır. Ayrıca konunun daha iyi anlaşılmasını sağlamak için farklı kaynaklardan da istifade edilmiştir.